Authority and Democracy in Corporate Governance? - Oosterhout, Hans van (Journal of business ethics, 2007)
Although McMahon offers a potentially valuable extension of Joseph Raz's conceptualization of authority by distinguishing three different kinds of authority, this paper argues, first, that his account of the conditions and considerations that would justify managerial authority is problematic because it relies on a conception of reasons for action that excludes precisely the kind of rationality that plays an important role in the␣explanation and justification of authority in economic␣organization. This paper explains, second, why McMahon's thesis of the justificatory similarity of authority in governments and nongovernmental organizations can also be seen to hold for corporate governance of publicly owned firms more specifically. Finally, this paper raises some critical objections against McMahon's presumption of democratic governance in governments and NGO's alike. The thrust of these objections is that democratic corporate governance does not make sense in the publicly owned firms because: (1) it will not produce results that are fair or welfare maximizing, and (2) it will undermine the legitimacy of managerial authority in such firms.